La isla de Abel - Steig, William, 1907-2003. (New York : Farrar, Straus, and Giroux, 1992)
Castaway on an uninhabited island, Abel, a very civilized mouse, finds his resourcefulness and endurance tested to the limit as he struggles to survive and return to his home.
Translation of : Abel's island.
"MIRASOL/libros juveniles."
Accelerated Reader AR
Newbery Honor, 1977.
Keywords: Mice -- Fiction; Islands -- Fiction; Survival -- Fiction; Spanish language materials